Impact Of Management System On Household Waste Utilization Potential - Loura Sari; John Bimasri; Etty Safriyani (Jurnal Multidisiplin Sahombu, 2025)
The increase in the volume of household waste is one of the pressing environmental issues, because poor management can cause air, soil, and water pollution, as well as cause various health problems. This study aims to optimize household waste processing in order to reduce the impact of environmental pollution. Which was carried out in Tugumulyo District, Musi Rawas Regency from October to December 2024. The study used a survey method with observation location points in 3 randomly selected areas ( Random sampling) , each point was determined 3 hamlets or neighborhood units randomly. Respondents were determined by simple random sampling as much as 15% of the number of families in each hamlet and RT. The data collected consisted of: 1) Respondent identity, 2) Amount and type of waste produced, 3) Type of waste storage inside and outside the home, and 4) household waste processing. The research data were processed tabulated using Microsoft Excel.2010 Software. The processed data were then analyzed mathematically and presented in the form of tabulations which were explained descriptively. The conclusion of this research is based on the results of the research that has been conducted, the following conclusions can be drawn: The type of waste that is mostly produced by households is organic waste, with an average waste production of 340 grams per day. Households mostly use temporary shelters both inside and outside the house in the form of plastic bags or plastic sacks. The amount of waste processed by the community is very small, which is only 6% of the total waste produced. The potential for utilizing household waste is very high, because it has not been processed much by the community.